Quality Of Life of Menopausal Women Suffering from Periodontitis Relating to Dental Conditions: Kualitas Hidup Perempuan Menopause Penderita Periodontitis, Berkaitan dengan Kondisi Gigi Geligi - Irma Ervina; Panggabean, Gabriel Jonathan; Pitu Wulandari; Martina Amalia (Dentika: Dental Journal, 2022)
Menopause describes the cessation of a woman’s menstrual period due to the ovaries’ shutdown of estrogen and progesterone production. Decreased levels of these hormones cause menopause symptoms and reduce the quality of life. Therefore, this study aims to determine how the quality of life of postmenopausal women and the practice of periodontics in Medan City are related to the condition of teeth. A descriptive method was used with a cross-sectional design to adapt the questionnaires. The number of samples was 60 people based on medical record data at the periodontics installation of the RSGM USU and dentists’ practice in Medan. Furthermore, a Likert scale was used to assess the quality of life of postmenopausal women with periodontitis. The results showed that the quality of life, which strongly influenced the teeth, was Stage IV Grade B. In terms of social relations, the most decisive influence on the condition of the teeth was appearance. The aspect of the physical ability which strongly influences the condition is chewing hard food. In conclusion, menopausal women with periodontitis influence their quality of life from aspects of physical ability, social relations, general health, and psychology. Key words: quality of life, menopausal women, periodontitis, dental conditions